DENTIFIKASI GASTROPODA DI SUB DAS ANAK SUNGAI GANDONG DESA KERIK TAKERAN - Tyas, Mustika Wahyuning; Widiyanto, Joko (Jurnal Florea, 2015)
The aim of research to determine the diversity and Gastropod that predominate in sub watershedtributary village Gandong Takeran Kerik. Descriptive qualitative research method with type ofobservational study. Determination and site selection studies using transect sampling method, thesize of 1x1 m transect quadrant. Research station at 3 stations with 3 points each station. The datawas analyzed after identifying the calculation dominance index and diversity index. Gastropodidentification results found 4 genera Thiara, Melanoides, Brotia, and Clea. The highest abundanceof gastropods at station II, namely 13.7 ind/m2. Thiara highest dominance index is 0.654, indicatingthat Thiara mendominansi in sub watershed tributary village Gandong Takeran Kerik. Diversityindex of each station 0.617, 0.765, and 0.615, indicating that the diversity of gastropods in subwatershed tributary village Gandong Takeran Kerik is very low. Environmental parameters airtemperature 30C - 31C, 28C - 29C water temperature, pH 7 to 7.3, and dissolved oxygen (DO) 5mg/l - 5,4mg /l.Keywords: Gastropod, diversity, GandongÂ